Rethinking the MBA : business education at a crossroads - Datar, Srikant M.; Cullen, Patrick G.; Garvin, David A. (Harvard Business Press, 2010)
Documents a chorus of concerns about business schools gleaned from interviews with deans and executives, and from an analysis of curricula and trends in graduate business education. This title provides case studies showing how leading MBA programs have begun reinventing themselves for the better